2006
DOI: 10.1089/dia.2006.8.636
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chromium Picolinate and Biotin Supplementation on Glycemic Control in Poorly Controlled Patients with Type 2 Diabetes Mellitus: A Placebo-Controlled, Double-Blinded, Randomized Trial

Abstract: This pilot study demonstrates that supplementation with a combination of chromium picolinate and biotin in poorly controlled patients with diabetes receiving antidiabetic therapy improved glucose management and several lipid measurements. Chromium picolinate/ biotin supplementation may represent an effective adjunctive nutritional therapy to people with poorly controlled diabetes with the potential for improving lipid metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 24 publications
2
52
0
Order By: Relevance
“…22 Cefalu et al (2010) 23 Chen et al (2014) 24 Crawford et al (1999) 25 Evans (1989) 26 Ghosh et al (2002) 27 Gunton et al (2005) 28 Grant and McMullen. (1982) 29 Grant et al (1997) 30 Hermann et al (1998) 31 Hermann et al (1994) 32 Jain et al (2012) 40 Lee and Reasner (1994) 41 Li et al (1992) 42 Li (1994) 43 45 Martinez et al (1985) 46 Mossop (1983) 47 Offenbacher and Pi-Sunyer (1980) 48 Offenbacher et al (1985) 49 Pasman et al (1997) 50 Pei et al (2006) 51 Rabinovitz et al (1983) 52 Rabinovitz et al (2004) 53 Racek et al (2006) 54 Riales et al (1981) 55 Singer and Geohas (2006) 56 Sharma et al (2011) 57 Sherman et al (1968) 58 Thomas and Gropper (1996) 59 Urberg and Zemel (1987) 60 …”
Section: Studies Measuring Hba1cmentioning
confidence: 99%
“…22 Cefalu et al (2010) 23 Chen et al (2014) 24 Crawford et al (1999) 25 Evans (1989) 26 Ghosh et al (2002) 27 Gunton et al (2005) 28 Grant and McMullen. (1982) 29 Grant et al (1997) 30 Hermann et al (1998) 31 Hermann et al (1994) 32 Jain et al (2012) 40 Lee and Reasner (1994) 41 Li et al (1992) 42 Li (1994) 43 45 Martinez et al (1985) 46 Mossop (1983) 47 Offenbacher and Pi-Sunyer (1980) 48 Offenbacher et al (1985) 49 Pasman et al (1997) 50 Pei et al (2006) 51 Rabinovitz et al (1983) 52 Rabinovitz et al (2004) 53 Racek et al (2006) 54 Riales et al (1981) 55 Singer and Geohas (2006) 56 Sharma et al (2011) 57 Sherman et al (1968) 58 Thomas and Gropper (1996) 59 Urberg and Zemel (1987) 60 …”
Section: Studies Measuring Hba1cmentioning
confidence: 99%
“…A recently reported 30-day pilot study [41] concluded that the combination of chromium picolinate and biotin improved short-term glycaemic control (oral glucose tolerance, fasting glucose, and fructosamine), and had a favourable effect on lipid parameters in subjects with type 2 DM. The study was a placebo-controlled 30-day intervention in obese to overweight subjects with poorly controlled type 2 DM, who were already receiving oral anti-diabetic medications (OADs).…”
Section: Introductionmentioning
confidence: 99%
“…Chromium has been found to reduce glucose intolerance and improve lipid levels in elderly diabetic patients 6 ; lower glucose levels, insulin resistance, and oxidative stress in obese patients with type 2 diabetes 7,8 ; and, in combination with biotin in poorly controlled diabetics, improves glucose management and lipid measurements. 9 However, a small trial (n ϭ 46) of obese, insulin-treated type 2 diabetics, chromium had no significant impact on glucose management after a 6-month trial. 10 The research on chromium supplementation for women with gestational diabetes is mixed.…”
Section: Discussionmentioning
confidence: 95%